2020
DOI: 10.18517/ijaseit.10.6.9110
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization of Rainfall-runoff Model GR4J using Particle Swarm Optimization on Planting Calendar

Abstract: Challenges in food production in the future are certainly more complex in developing countries like Indonesia. The Agricultural Research and Development Agency developed an Integrated Planting Calendar (Katam) information system to decide the water discharge for rice planting time using rainfall-runoff modeling called GR4J (Genie Rural a four parameters Journalier). This study aims to improve the accuracy of the GR4J model for determining water discharge in an area. The study areas in this study were the Progo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…[33] Also, the ordinary version of the classifier in the high school selection dataset for students of SMP Islam Al-Hikmah Pondok Cabe proved that the accuracy rate had increased by 7.36% after the application's optimization of the GA (genetic algorithm) method. Furthermore, [34] and [35] also observed that the Particle Swarm Optimization (PSO) technique was proven to produce a better level of accuracy.…”
Section: Literature Review Of Optimization Effortsmentioning
confidence: 99%
“…[33] Also, the ordinary version of the classifier in the high school selection dataset for students of SMP Islam Al-Hikmah Pondok Cabe proved that the accuracy rate had increased by 7.36% after the application's optimization of the GA (genetic algorithm) method. Furthermore, [34] and [35] also observed that the Particle Swarm Optimization (PSO) technique was proven to produce a better level of accuracy.…”
Section: Literature Review Of Optimization Effortsmentioning
confidence: 99%
“…It has been verified in more than 400 regions with different climatic conditions after continuous improvement and development by hydrological scholars (Perrin et al, 2003;Moine et al, 2008). So far, the model has been widely used in water resources management, flood forecasting, and low flow forecasting in global catchments (Dhemi et al, 2010;Aufar and Sitanggang, 2020). The GR4J model is divided into two modules: production store and routing store, and both of them are calculated by a nonlinear reservoir.…”
Section: Gr4j Modelmentioning
confidence: 99%